1970
DOI: 10.1901/jaba.1970.3-149
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Extreme Social Isolation by Contingent Social Reinforcement

Abstract: Two socially isolated patients were placed on a program where social reinforcement from staff members was made dependent on social interaction with other patients or staff members. This procedure was imposed in a setting where only limited control was possible. The level of social interaction and a concomitant alternate behavior in each patient was increased when the contingency for social reinforcement was imposed. The study provides another example of the efficacy of social reinforcement where there is littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Observation of the dependent variable alone will allow unambiguous conclusions about changes in the target behavior, but it will not allow conclusions about the source of those changes (Billingsley, White, & Munson, 1980 (Milby, 1970;Reisinger, 1972;and Kazdin, 1973, respectively), but no such rigor is applied to the same behaviors when they appear as antecedents or consequences to the target behavior, as independent variables (Strain, Shores, & Timm, 1977;Dorsey, Iwata, Ong, & McSween, 1980;and Hasazi & Hasazi, 1972, respectively Romanczyk et al, 1973). Finally, Hersen (1981) (Reid, 1970 Stallings, 1975), noted that many of Stallings' findings would be uninterpretable without the examination of the actual (not the planned) application of the independent variable.…”
Section: Methodological Statements On Independent Variable Accuracymentioning
confidence: 99%
“…Observation of the dependent variable alone will allow unambiguous conclusions about changes in the target behavior, but it will not allow conclusions about the source of those changes (Billingsley, White, & Munson, 1980 (Milby, 1970;Reisinger, 1972;and Kazdin, 1973, respectively), but no such rigor is applied to the same behaviors when they appear as antecedents or consequences to the target behavior, as independent variables (Strain, Shores, & Timm, 1977;Dorsey, Iwata, Ong, & McSween, 1980;and Hasazi & Hasazi, 1972, respectively Romanczyk et al, 1973). Finally, Hersen (1981) (Reid, 1970 Stallings, 1975), noted that many of Stallings' findings would be uninterpretable without the examination of the actual (not the planned) application of the independent variable.…”
Section: Methodological Statements On Independent Variable Accuracymentioning
confidence: 99%
“…The three most commonly used methods of identifying withdrawn children and measuring interactive behavior are based upon (a) sociometric (peer rating) measures (Marshall, 1957;Amidon, 1961;Bonney, 1971;Gottman, Gonso, & Rasmussen, 1975); (b) behavioral observation measures of social interaction frequency or duration (Allen, Hart, Buell, Harris, & Wolf, 1964;Kirby & Toler, 1970;Milby, 1970;O'Connor, 1969O'Connor, , 1972Walker & Hops, 1973); and (c) teacher nominations or ratings (Walker, 1970;Walker, 1973;Greenwood, Walker, Todd, & Hops, 1976), respectively. To the authors' knowledge, few, if any, studies have been conducted in which the validity, efficiency, and/or accuracy of these three measures have been compared directly in their ability to predict outside criterion measures of social competence.…”
Section: Interaction Assessment Methodsmentioning
confidence: 99%
“…In recent years considerable attention has been given to increasing the social skills of withdrawn psychiatric patients. A large variety of operant techniques have been used to foster and stimulate social interaction in these patients (2,13,14,16,17).…”
Section: Problemmentioning
confidence: 99%
“…
PROBLEMIn recent years considerable attention has been given to increasing the social skills of withdrawn psychiatric patients. A large variety of operant techniques have been used to foster and stimulate social interaction in these patients (2,13,14,16,17).In most of the studies reported efforts were at the experimental level and were conducted primarily for demonstrational purposes. Thus, the specific behavioral strategies used clinically in a comprehensive approach to the development and maintenance of social functioning in the withdrawn patient have not been documented as yet.
…”
mentioning
confidence: 99%